# If pth,qth and rth terms of an A.P. are a,b, c respectively, then show that a(q - r)+b(r - p)+c(p - q) = 0

1

2015-02-18T20:06:03+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let a = first term of the AP.
and
Let d = common difference of the AP

Now
a = A+(p-1).d.......(1)
b = A+(q-1).d.......(2)
c = A+(r-1).d........(3)

Subtracting 2nd from 1st , 3rd from 2nd and 1st from 3rd we get

a-b = (p-q).d......(4)
b-c = (q-r).d........(5)
c-a = (r-p).d.......(6)

multiply 4,5,6 by c,a,b respectively we have

c.(a-b) = c.(p-q).d......(4)
a.(b-c) = a.(q-r).d........(5)
b.(c-a) = b.(r-p).d.......(6)

a(q-r).d+b(r-p).d+c(p-q).d = 0(a(q-r)+b(r-p)+c(p-q)).d = 0

Now since d is common difference it should be non zero

Hence
a(q-r)+b(r-p)+c(p-q)= 0